Analysis of the Osseointegration Process of Dental Implants by Electron Paramagnetic Resonance: An In Vivo Study - Elena Kalinnikova; Margarita Sadovnikova; Alexander Rodionov; Fadis Murzakhanov; Peter Grishin (MDPI AG, 2022)
This research work presents an analysis of the process of an implant's osseointegration to the jawbone tissue. The purpose of this work was to describe the processes of assimilation and the biochemical dynamics which occur during dental implantation using implants with different macro-microstructure surfaces at the level of stable free radicals using the electron paramagnetic resonance (EPR) method. The experimental investigation was conducted on seven Vietnamese minipigs over twelve months old and weighing up to 30 kg using implants with various macro-microstructure surfaces (SLA, RBM, and HSTTM) and implantation systems, namely the Adin, Sunran, Biomed, and Osstem systems. The integration of the implant into the bone triggered biochemical processes with the formation of stable free radicals. The EPR method was used to identify the formed paramagnetic species and to study the dynamics of the interaction between the surface of the implant and the bone after one and two months. The concentration of carbonate surface centers increased with the time that the implant was connected to the hard tissue. The "Sunran" and "HSTTM" were established as the most suitable implantation system and surface type, respectively, thanks to the highest rate of osseointegration (assimilation) with the bone (hard) tissue. Thus, the EPR method provides the opportunity to study implantation processes.